Don Juan: the Discourse of Seduction as an Exercise of Power - Stankevičiūtė, Kristina (Respectus Philologicus, 2016)
The figure of Don Juan that emerged in Spanish baroque synthesised several important cultural issues related to the phenomenon of seduction, a subject of great social controversy since the very beginning of the Christian era. The present article analyses one of the fundamental parts of the universal appeal of the Don Juan figure – the discourse of seduction, considering it from the social and cultural point of view. The traditional discussion of the subject focuses on the contents of the discourse whereas the present article emphasises the implications rather than the contents, grounding its arguments on Jean Baudrillard’s theory of seduction, which claims that it is the signs and the play of signs that are important in seduction, not their meanings. The seduction discourse is seen as a means to exercise power on the women that Don Juan deals with as well as on the audience who gets involved into the discourse creation process. The article concludes with a claim that Don Juan is a figure of social domination, and his discourse is a means to achieve it.
Keywords: Don Juan; Seduction; Discourse; Power